1994
DOI: 10.1172/jci117162
|View full text |Cite
|
Sign up to set email alerts
|

Activation of H+ conductance in neutrophils requires assembly of components of the respiratory burst oxidase but not its redox function.

Abstract: In phagocytes, superoxide generation by the NADPH oxidase is accompanied by metabolic acid production. Cytoplasmic acidification during this metabolic burst is prevented by a combination of H+ extrusion mechanisms, including a unique H+ conductance. NADPH oxidase is deficient in chronic granulomatous disease (CGD) patients. The burst of acid production is absent in CGD patients lacking the 47-kD (p47-phox) or the 91-kD (gp9l-phox) subunits of the oxidase. Activation of the H+ conductance is also defective in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
(14 reference statements)
1
30
0
Order By: Relevance
“…It is doubtful whether a protein highly specific for phagocytic cells could be responsible for the electrogenic H+-movements of embryologically so distinct cell types. Finally, our data are in good agreement with recent findings on CGD patients' neutrophils, in which a H + conductance activated by depolarisation and internal acidification has been detected despite of absence of gp91pho× [30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is doubtful whether a protein highly specific for phagocytic cells could be responsible for the electrogenic H+-movements of embryologically so distinct cell types. Finally, our data are in good agreement with recent findings on CGD patients' neutrophils, in which a H + conductance activated by depolarisation and internal acidification has been detected despite of absence of gp91pho× [30].…”
Section: Discussionsupporting
confidence: 93%
“…T and B cells" H +-movements through the plasma membrane of T and B lymphocytes prepared from human tonsils were measured by monitoring intracellular pH changes with the same technique as used for the characterization of the electrogenic H +-transporting pathway of neutrophil granulocytes, peripheral lymphocytes, macrophages and enterocytes [4,7,11,16,23]. Briefly, intracellular pH was measured on the basis of the fluorescence of the pH indicator dye BCECF.…”
Section: Measurement Of H+-movements Through the Plasma Membrane Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure to see H ϩ current at pH i 7.5 is especially surprising, because the currents at pH i 6.9 are an order of magnitude greater than in any mammalian cell. Finally, the outward currents in CHO cells activate anomalously rapidly, within Ͻ100 ms, whereas act for phagocyte H ϩ channels is typically seconds (9,17,24,27,29,31). It was reported recently that transient gp91 phox expression in COS-7 cells results in voltage-gated proton currents (15).…”
Section: Gp91 Phox Is Not a Proton Channel In Phagocytes 36065mentioning
confidence: 99%
“…Several lines of evidence have suggested that the gp91 phox component of the NADPH oxidase complex might be the proton channel that is activated during the respiratory burst (2,3,7,8). The presence of H ϩ currents in monocytes from gp91 phox -deficient CGD 1 patients appeared to refute this idea (9), but Henderson and Chappell (10) argued that these data were inconclusive. Furthermore, it has been reported that heterologous expression of gp91 phox results in the appearance of proton fluxes or proton currents resembling those activated during the respiratory burst (8,(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%